The Effect Of Influencer Marketing And Campaign Missions On Purchasing Decisions At Market Place (Shopee) (Study At University Of Darussalam Gontor) - Ni'mah, Fifi Nur Fidiya (University of Darussalam Gontor, 2024)
This research aims to analyze the effect of influencer marketing and campaign missions on consumer purchasing decisions in the Shopee marketplace among students at University of Darussalam Gontor. This research uses quantitative methods to analyze collected data and tested using multiple linear regression analysis. This research used 200 respondents from female students who used the Shopee marketplace. The results of this research state that the influencer marketing (X1) and campaign mission (X2) variables influence consumer purchasing decisions (Y). with the resulting Adjusted R-Square of 54.5% and the remaining 45.5% influenced by other variables.